Physiologycal Systems in Insects. - Klowden, M J (London : Academic pree, 2007)
Discusses the roles of molecular biology, neuroendocrinology, biochemistry, and genetics in our understanding of insects. This title includes the details from the literature on hormone receptors, behavioral genetics, insect genomics, neural integration, and more.
Includes bibliographical references.; Glossary 643-660p.; Index 661-688p.
Keywords: Insects- physiology; Zoology